The Senses in the Music Tragedy by Quinault and Lully (Itinera, 2017)
If the show has authority to educate, the instruction is softened by the pleasure of the senses. In this vein, Quinault is perfectly representative of his time. Playwright was appreciated in Paris, he invents with Lully the tragedy in music which multiplies tenfold the reception and the pleasure of the senses at the spectator. We propose from then on a reflection on the senses in the tragedy in music of Quinault and Lully, of Cadmus (1673) to Armide (1686).